2013
DOI: 10.1002/ijc.28580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of p16-immunopositive but HPV DNA-negative oropharyngeal carcinomas

Abstract: Recent studies have reported that p16 protein overexpression qualifies as a surrogate marker identifying an oncogenic human papillomavirus (HPV) infection in oropharyngeal squamous cell carcinoma (OPSCC). However, there is still a percentage of OPSCCs that are positive for p16 immunohistochemistry (p16 IHC) but lack HPV DNA. The objective of this study was to characterize this group at the molecular level by performing sensitive HPV DNA-and RNA-based PCR methods and genetic profiling. All patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 28 publications
6
100
2
1
Order By: Relevance
“…Another study stated that HPV DNA-negative but p16-immunopositive cases are actually HPV-negative, based on genetic profiling. It was revealed that the survival rates of these patients was the same as that of HPV-negative patients, which indicated the significance of testing for HPV DNA along with immunostaining to check for HPV positive oral cancers [29]. Similarly, one more study showed p16-IHC/DNA qPCR to be more sensitive and specific (97% and 94% respectively) as compared to RNA qPCR, proving to be the best contradistinguishing test for a suitable outcome.…”
Section: Discussionmentioning
confidence: 86%
“…Another study stated that HPV DNA-negative but p16-immunopositive cases are actually HPV-negative, based on genetic profiling. It was revealed that the survival rates of these patients was the same as that of HPV-negative patients, which indicated the significance of testing for HPV DNA along with immunostaining to check for HPV positive oral cancers [29]. Similarly, one more study showed p16-IHC/DNA qPCR to be more sensitive and specific (97% and 94% respectively) as compared to RNA qPCR, proving to be the best contradistinguishing test for a suitable outcome.…”
Section: Discussionmentioning
confidence: 86%
“…Owing to its numerous advantages, p16 immunohistochemistry (Table 1) has emerged as a key test to define HPV status and prognosis in a clinical setting. 3,8 However, it is clearly acknowledged that ∼ 8-20% of p16-positive oropharyngeal squamous cell carcinomas are HPV-negatives [10][11][12] and this is even more problematic in other upper aerodigestive anatomical subsites, where p16's positive predictive value drops significantly. 25 This highlights the absence of a direct and exclusive link between HPV infection, p16 over-expression, and carcinogenesis and suggests that non-viral mechanisms may have a role in p16 over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several authors have reported that ∼ 8-20% of p16-positive oropharyngeal squamous cell carcinomas do not contain HPV-DNA and have a molecular profile that is closer to HPV-negative cancers. [10][11][12] In this context, determining the presence and activity of HPV with a single test is very attractive. The RNAscope HPV-test (Advanced Cell Diagnostics, Hayward, CA, USA) is a recent in situ hybridization technique that detects E6/E7 mRNA from up to 18 high-risk HPVs (HPV16, 18, 26, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68, 73, and 82).…”
mentioning
confidence: 99%
“…However, p16 immunohistochemistry is not an ideal surrogate marker for an HPV infection because a considerable percentage of patients are p16-positive but HPV-negative. 17,28 The application of p16 protein overexpression as a surrogate marker for HPV infection could have affected their results. In our institution, we use a validated algorithm for HPV detection: p16 immunostaining, followed by a general primer 5ϩ/6 polymerase chain reaction on the p16-immunopositive cases.…”
Section: Discussionmentioning
confidence: 99%